Variants of WDR36 in Cameroonian glaucoma patients - Fanny Mbacham; Yannick Bilong; Jean Paul Chedjou; Arlette Nomo; Chantal Nanfack Ngoune; Hermann Dongmo; CalvinoTAH; Jean-Claude Katte; Wilfred Mbacham; Eugene SobngwI; Assumpta Lucienne Bella (Archive of Biomedical Science and Engineering - Peertechz Publications, 2020)
Background: In Primary Open Angle Glaucoma (POAG), the most common form of glaucoma in people of African origin, it is established that retinal ganglion cells are lost due to apoptosis. Loss of WDR36 (OMIM 609669) function has been shown to result in activation of the p53 stress-response pathway, a key regulator of apoptosis. However, there is controversy surrounding its contribution in the pathogenesis of POAG. We aimed to establish an association between 3 WDR36 gene polymorphisms and POAG. Methods: We assessed 798 glaucoma medical records and selected 209 POAG cases. A total of 26 POAG cases residing in Yaoundé completed the study and 19 controls were matched for age and gender. Dried blood spots on Whatman filter paper grade 3 were used for DNA extraction by the Chelex method. Polymerase Chain Reaction (PCR) was conducted with two sets of primers on rs1971050, rs10038177 and rs10038058 followed by Restriction Fragment Length Polymorphism (RFLP) using restriction enzymes AluI on rs1971050, rs10038177and ApoI on rs10038058 to determine the genotypes.  Results: After digestion, the homozygous mutant form of rs1971050 was evidenced in both groups of our study population T/T (100%). The T and the A alleles were the most common alleles found in our study population and were not associated with POAG. Heterozygote and homozygote mutant genotypes were obtained in both groups for rs10038177 (POAG group C/T (7.7%) and T/T (92.3%) and in the control group C/T (10.5%) and T/T (89.5%)) and rs10038058 (G/A (11.5%) and A/A (88.5%) genotypes in the POAG group and in the control group G/A (10.5%) and A/A (89.5%)). These genotypes were not associated with Primary Open Angle Glaucoma (POAG).  Conclusion: Homozygous mutant genotypes of rs1971050, rs10038177 and rs10038058 may not be associated with the disease process of primary open angle glaucoma in Cameroon.